2015
DOI: 10.2308/acch-51187
|View full text |Cite
|
Sign up to set email alerts
|

Restatements: Do They Affect Auditor Reputation for Quality?

Abstract: SYNOPSIS We examine whether an auditor's involvement with a financial statement restatement has a negative effect on their reputation as evidenced by both clients' and the market's assessments of audit firm quality. Specifically, we investigate the effect of auditor involvement with restatements on the non-restating clients' likelihood to dismiss their auditors in the year subsequent to restatement and on non-restating clients' market adjusted returns (MARs) around the restatement announcement d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…Previous research provides evidence that a company's decision to dismiss its incumbent auditor is sensitive to observable audit failures of the incumbent auditor. These audit failures include restatements by the auditor's other clients (Irani et al ; Swanquist and Whited ), SEC disciplinary actions (Wilson and Grimlund ), the events surrounding the collapse of Arthur Andersen LLP (Barton ; Chen and Zhou ), and other highly publicized audit failures (Skinner and Srinivasan ; Weber et al ). Overall, previous research supports the agency theory view and demonstrates that a reputation for low audit quality is positively associated with subsequent dismissal by audit clients that were not subject to the observed audit failures (e.g., did not restate their financial statements).…”
Section: Background and Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research provides evidence that a company's decision to dismiss its incumbent auditor is sensitive to observable audit failures of the incumbent auditor. These audit failures include restatements by the auditor's other clients (Irani et al ; Swanquist and Whited ), SEC disciplinary actions (Wilson and Grimlund ), the events surrounding the collapse of Arthur Andersen LLP (Barton ; Chen and Zhou ), and other highly publicized audit failures (Skinner and Srinivasan ; Weber et al ). Overall, previous research supports the agency theory view and demonstrates that a reputation for low audit quality is positively associated with subsequent dismissal by audit clients that were not subject to the observed audit failures (e.g., did not restate their financial statements).…”
Section: Background and Hypotheses Developmentmentioning
confidence: 99%
“…Given the limited evidence of any stakeholder response, I consider a second research question: should stakeholders respond to Type II GCO errors? To address this question, I examine the association between Type II GCO errors and restatements, an established measure of low audit quality (Aobdia ; Christensen et al ; DeFond and Zhang ; Francis and Michas ; Irani et al ; Swanquist and Whited ). I model the probability of subsequent restatement at the company‐year level as a function of an audit office's Type II GCO errors (Eshleman and Guo ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, if accounting firm ranks capture meaningful information about audit quality, they should have an economic impact on the audit market, via auditor selection and audit fees. Prior literature suggests that accounting firms with more audit failures are more likely to be dismissed by clients (Hennes, Leone, & Miller, 2014;Irani, Tate, & Xu, 2015;Swanquist & Whited, 2015), and high-quality audit services are an important product differentiation strategy that allows auditors to earn higher audit fees (Craswell, Francis, & Taylor, 1995;Francis, Reichelt, & Wang, 2005). Blankley, Hurtt, and MacGregor (2012) indicated that audit fees are generally indicative of the level of audit effort exerted, suggesting that higher audit fees indicate an increase in the level of service provided.…”
Section: Related Studies and Research Questionsmentioning
confidence: 99%
“…A statistically significant result can be economically unimportant, and the opposite can be true for an insignificant finding. Irani, Tate, and Xu (2015) explicitly recognized this issue. They stated (Irani et al 2015, p. 847; emphasis added): ''We recognize the small magnitude of the univariate market reaction, which, although statistically significant, is arguably not economically significant.''…”
Section: The Regression Storymentioning
confidence: 99%